PENERAPAN TERAPI MUROTTAL AL-QUR’AN DAN RELAKSASI NAFAS DALAM TERHADAP PENURUNAN TINGKAT KECEMASAN KLIEN PRE OPERASI FRAKTUR FEMUR DENGAN TINDAKAN ORIF DI RUMAH SAKIT ISLAM PURWOKERTO - Desi Ayuningsih; Suci Khasanah (Jurnal Cakrawala Ilmiah, 2023)
Anxiety occurs in many clients before surgery. The application of murattal Al-Qur’an therapy and deep breathing relaxation is a type of non-pharmacological therapy. The purpose of this case study was to determine the application of murattal therapy and deep breathing relaxation to reduce preoperative anxiety levels of femur fractures in the intraoperative room of Purwokerto Islamic Hospital. The sample in this case is the pretest-posttest using The Amsterdam Preoperative Anxiety and Information Scale (APAIS) instrument. It was concluded that murattal therapy and deep breathing relaxation can reduce anxiety levels in preoperative patients. Based on the results of the case study it is recommended to use this type of treatment in an effort to reduce the anxiety of oraoperative patients.